2012
DOI: 10.1248/cpb.c12-00506
|View full text |Cite
|
Sign up to set email alerts
|

Induction of G1 Arrest and Apoptosis in Human Cancer Cells by Crebanine, an Alkaloid from <i>Stephania venosa</i>

Abstract: In this study, we focused the effects of crebanine, an alkaloid isolated from the tuber of Stephania venosa, on various human cancer cells. Crebanine treatment was found to significantly inhibit the proliferation of human leukemic cells (HL-60, U937 and K562), human fibrosarcoma cells (HT1080) and cervix cancer cell lines (KB-3-1 and KB-V1), of which HL-60 cells were the most sensitive to its treatment. In contrast, crebanine caused much less toxicity in human normal fibroblast cells. Our results demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Crebanine exhibits a variety of biological properties including, anti-microbial activities, improvement of neurodegenerative diseases, as well as antiinvasion and anti-proliferation activities in cancer cells. [14][15][16] Moreover, our previous report demonstrated that crebanine reduced TNF-α induced lung cancer cells proliferation and invasion via suppressing NF-κB activity.…”
Section: 13)mentioning
confidence: 97%
“…Crebanine exhibits a variety of biological properties including, anti-microbial activities, improvement of neurodegenerative diseases, as well as antiinvasion and anti-proliferation activities in cancer cells. [14][15][16] Moreover, our previous report demonstrated that crebanine reduced TNF-α induced lung cancer cells proliferation and invasion via suppressing NF-κB activity.…”
Section: 13)mentioning
confidence: 97%
“…Additionally, it was also shown in the same study that presence of a free phenolic function at C-6 or C-7 show significantly high cytotoxicity toward the KB cancer cell line as in the case of some of the alkaloids. In this same cell line, another alkaloid-crebanine, isolated from the tuber of Stephania venosa, has also been investigated for its anticancer properties in vitro (Wongsirisin et al, 2012). Here, cells treated with 70.7 μM of crebanine for 48 h demonstrated inhibition in cell growth, with the IC 50 of 24 μg/mL.…”
Section: Alkaloidsmentioning
confidence: 99%
“…The phytochemical studies on this genus have indicated the isoquinoline alkaloids as the main chemical constituents with over 200 of which have been described (Semwal et al, 2010). Many of these constituents have important pharmacological activities including anti-proliferative (Bun et al, 2009;Nantapap et al, 2010;Wongsirisin et al, 2012), antimalarial (Likhitwitayawuid et al, 1993), antimicrobial (Deng et al, 2011), acetylcholinesterase-inhibiting (Tran et al, 2010), antihyperglycemic (Tsutsumi et al, 2003) and antiprotozoal activities (Camacho et al, 2000). The extracts of the tubes of S. venosa and their aporphine alkaloids isolated (e.g.…”
Section: Introductionmentioning
confidence: 99%